A Feasibility study on QUALITECH Integrated Coconut Processing System - Chiu, Lirie W.; Lam, Anna Grace A.; Lorenzo, Carlo Ryan R.; Monoy, Darlene C. (College of Engineering, 1999)
QUALITECH Integrated Coconut Processing System (ICPS) is a processing system for coconut parts. It is made up of three machines: the decorticator, carbonizer, and the mechanical dryer. The decorticator produces coir fiber from husk, the carbonizer converts coconut shell into charcoal and the mechanical dryer converts meat into copra. The QUALITECH ICPS is different from the other existing machines. It can manufacture almost all of the main parts of a coconut except for the coconut water. Because of this, the ICPS can increase the output of coconut farmers. At 8 hours per day of operation, the ICPS can progress 4000 kilograms of copra, 2000 kilograms of coir fiber and 1000 kilograms of coconut shell charcoal. It definitely has a greater capacity compared to the existing methods. Unlike the present manual methods, the ICPS is less labor-intensive. The machines will do most of the processing of the coconut parts. All the farmers have to do is to monitor the machines. Therefore, the ICPS can increase the income of coconut farmers. From the result of the market segmentation, the coconut cooperatives will be the target market of the ICPS. At present, there are no other fabricators of ICPS. The demand for the ICPS is determined from the demand for copra, coir fiber and charcoal, the output products that will be processed by the ICPS. Survey results showed that 100% of the respondents are willing to buy the ICPS. The proposed plant will have a sales plan of 24 units per year since it takes one month to produce one unit of ICPS. From this, the market share was determined to be 1.054% for the first year and this will increase up to 1.063% for year 5. The selling price of ICPS is determined from the market survey conducted. It is pegged at P2.8 million. The marketing budget for the first year is P 1,198,000. It consists of printing expenses for the brochures, trade fairs participation, salary and traveling expenses of sales representatives and advertisements in Agriculture magazines and newspapers. This marketing budget will be increased by 10% every year. The major processes in fabricating the ICPS are welding, cutting, grinding, drilling, bending, and rolling. The fabrication process is labor-dependent. Gantt charts are used to determine the labor and machine requirements. The total number of welders needed is six and 15 for the helpers. In order to meet the sales plan, the result of the aggregate planning shows that it is more feasible to add a second shift for the carbonizer and mechanical dryer sections.